1977
DOI: 10.1042/bj1610405
|View full text |Cite
|
Sign up to set email alerts
|

The disulphide-bonded nature of procollagen and the role of the extension peptides in the assembly of the molecule

Abstract: 1. The molecular weights of chick tendon and cartilage procollagens, and their constituent polypeptides, were determined by gel filtration and gel electrophoresis. The values obtained are in good agreement and indicate that the mol.wts. of the secreted procollagens (types I and II) and their individual pro-alpha-chains are of the order of 405 000-445 000 and 137 000-145 000 respectively.2. Digestion of tendon procollagen with human rheumatoid synovial collagenase gave products consistent with the presence of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…This result correlates well with the synthesis of pro-al and pro-a2 chains in a 2: 1 ratio observed in calvaria (Fessler et al, 1975), tendon cells (Harwood et al, 1977) and in studies with collagen-synthesizing polyribosomes (Kerwar et al, 1972;Vuust, 1975). However, in the wheatgerm system the very faint bands corresponding to bands A and B were not in a 2: 1 ratio.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This result correlates well with the synthesis of pro-al and pro-a2 chains in a 2: 1 ratio observed in calvaria (Fessler et al, 1975), tendon cells (Harwood et al, 1977) and in studies with collagen-synthesizing polyribosomes (Kerwar et al, 1972;Vuust, 1975). However, in the wheatgerm system the very faint bands corresponding to bands A and B were not in a 2: 1 ratio.…”
Section: Discussionsupporting
confidence: 68%
“…However, since the translation products do not undergo hydroxylation in the reticulocyte-lysate system (Table 2), the cell-free products might be expected to migrate in positions corresponding to unhydroxylated pro-a1 and unhydroxylated pro-a2 chains, which have been shown to migrate faster than the corresponding hydroxylated polypeptide in composite agarose/polyacrylamide gels (Harwood et al, 1977). This difference in mobility between hydroxylated and unhydroxylated pro-a chains is also demonstrable in SDS/polyacrylamide gels (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the available evidence algo suggested that glycoprotein MFP I was unlike any type of collagen or procollagen hitherto characterized. In particular, the solubility of glycoprotein MFP I in 30%-saturated (NH4)2SO4 distinguishes it from type-I, -II and -III procollagen species, which are insoluble under such conditions (Olsen et al, 1976;Harwood et al, 1977;Scott et al, 1977;Uitto, 1977). This observation suggests that glycoprotein MFP I is much more highly glycosylated than are the interstitial collagen precursors, a possibility that is supported by several other findings, including the ease with which glycoprotein MFP I is labelled with [3Hlfucose, its avidity for the periodic acid-Schiff reagent and its high content of hydroxylysine (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By removing the tendon extracellular matrix by digestion with bacterial collagenase, tendon fibroblasts are released into suspension (approx 3 · 10 6 cells per embryo) and for 4-6 h in culture they will continue to synthesize and secrete the soluble collagen precursor, procollagen (Dehm et al 1972). This molecule was eventually shown to possess N-and C-terminal extensions to the collagen helix, which confer solubility on the procollagen molecule and play a significant role in helix formation and fibre assembly (Harwood et al 1977;Prockop et al 1979). I was fortunate to join the Prockop laboratory in September 1970, on leave from my position in Manchester, and as a joint post-doc with Dr Nicholas Kefalides we resolved to investigate the synthesis of the collagenous proteins associated with the basement membrane structure which forms the lens capsule.…”
Section: Collagen Synthesis and New Collagen Typesmentioning
confidence: 99%